Chromatographic Fingerprint Analysis of Marrubiin in Marrubium vulgare L. via HPTLC Technique - Keyvan Yousefi; Sanaz Hamedeyazdan; Mohammadali Torbati; Fatemeh Fathiazad (Tabriz University of Medical Sciences, 2016)
Purpose: In the present study we aimed to quantify marrubiin, as the major active compound, in the aerial parts of Marrubium vulgare from Iran using a HPTLC-densitometry technique. Methods: Quantitative determination of marrubiin in M. vulgare methanol extract was performed by HPTLC analysis via a fully automated TLC scanner. Later on, the in vitro antioxidant activity of the M. vulgare methanol extract was determined using 1,1-diphenyl-2-picryl-hydrazil (DPPH) free radical scavenging assay. Furthermore, total phenolics and flavonoids contents of the methanol extract were quantified, spectrophotometrically. Results: The amount of marrubiin was calculated as 156 mg/g of M. vulgare extract. The antioxidant assay revealed a strong radical scavenging activity for the M. vulgare methanol extract with RC50 value of 8.24μg/mL. Total phenolics and flavonoids contents for M. vulgare were determined as 60.4 mg gallic acid equivalent and 12.05 mg quercetin equivalent per each gram of the extract, correspondingly. Conclusion: The presented fingerprint of marrubiin in M. vulgare extract developed by HPTLC densitometry afforded a detailed chemical profile, which might be useful in the identification as well as quality evaluation of herbal medications based on M. vulgare. Besides, the considerable antioxidant activity of M. vulgare was associated with the presence of marrubiin along with phenolics and flavonoids exerting a synergistic effect.